Respuesta :

Answer:

[tex]a_0=0; \; a_n=2^n-1 \; (n>0)[/tex]

Step-by-step explanation:

[tex]a_0=0[/tex]

[tex]a_1=2a_0+1=1[/tex]

[tex]a_2=2a_1+1=3=1+2[/tex]

[tex]a_3=2a_2+1=7=1+2+4[/tex]

[tex]a_4=2a_3+1=15=1+2+4+8[/tex]

[tex]a_5=2a_4+1=31=1+2+4+8+16[/tex]

So, we can infer that

[tex]a_n=1+2^1+2^2+2^3+...+2^{n-1}[/tex]

and we only need to find out a formula for this sum (a geometric reason with common ratio 2)

Let's call

[tex]S=1+2^1+2^2+...2^{n-1}[/tex]

then,

[tex]2S=2+2^2+...2^{n-1}+2^n[/tex]

hence,

[tex]S-2S=1-2^n[/tex]

[tex]2S-S=S=2^n-1[/tex]

and we have our closed formula for the sequence

[tex]a_0=0; \; a_n=2^n-1 \; (n>0)[/tex]

ACCESS MORE